Participant retention practices in longitudinal clinical research studies with high retention rates. Issue 1 (December 2017) - Abshire, Martha; Dinglas, Victor; Cajita, Maan; Eakin, Michelle; Needham, Dale; Himmelfarb, Cheryl
Abstract Background There is a need for improving cohort retention in longitudinal studies. Our objective was to identify cohort retention strategies and implementation approaches used in studies with high retention rates. Methods Longitudinal studies with ≥200 participants, ≥80% retention rates over ≥1 year of follow-up were queried from an Institutional Review Board database at a large research-intensive U.S. university; additional studies were identified through networking. Nineteen (86%) of 22 eligible studies agreed to participate. Through in-depth semi-structured interviews, participants provided retention strategies based on themes identified from previous literature reviews. Synthesis of data was completed by a multidisciplinary team. Results The most commonly used retention strategies were: study reminders, study visit characteristics, emphasizing study benefits, and contact/scheduling strategies. The research teams were well-functioning, organized, and persistent. Additionally, teams tailored their strategies to their participants, often adapting and innovating their approaches. Conclusions These studies included specialized and persistent teams and utilized tailored strategies specific to their cohort and individual participants. Studies' written protocols and published manuscripts often did not reflect the varied strategies employed and adapted through the duration of study. Appropriate retention strategy use requires cultural sensitivity and more research is needed to identify how strategy use varies globally.